2021
DOI: 10.3390/en14030624
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approach to the Design, Manufacturing and Examination of Gerotor and Orbital Hydraulic Machines

Abstract: Gerotor technology is an important research area in the field of hydraulics which attracts the attention of both academic scientists and industry. Despite the numerous publications announced by academics, as well as a considerable number of projects made by industry, the subject has not been exhausted. This paper presents a new approach to gerotor technology which has been formed by gathering the authors’ knowledge of gerotors in a synthetic form. The following scientific and technical results have been obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It was confirmed that the oscillator-cavitation system, designed and manufactured on the basis of [20,22], is useful for inducing the phenomenon of ultrasonic cavitation. It was also confirmed that the PIV visualization method based on a special system of illuminating transparent objects and recording the flow through those objects by means of a fast camera are useful in the research on the cavitation phenomena [24,26].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…It was confirmed that the oscillator-cavitation system, designed and manufactured on the basis of [20,22], is useful for inducing the phenomenon of ultrasonic cavitation. It was also confirmed that the PIV visualization method based on a special system of illuminating transparent objects and recording the flow through those objects by means of a fast camera are useful in the research on the cavitation phenomena [24,26].…”
Section: Discussionmentioning
confidence: 68%
“…Thus, it can be concluded that the use of the ultrasonic cavitation and the oil degasification leads to the reduction of the hydrodynamic cavitation. Further limitation of the phenomena of the hydrodynamic cavitation in a gear pump is achieved by design methods, through the application of relief grooves [14,26].…”
Section: Visualization Tests Of the Cavitation Test Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis is performed on both epitrochoidal and hypotrochoidal profiles by taking two non-dimensional parameters related to a geometric approach that supported the law of gearing and developed synthetic equations. Jaros1aw and Piotr 4 has also proposed a synthetic approach to design, manufacturing and also examination of gerotor and orbital hydraulic machines. Sasaki et al 5 had established a new tooth shape named 'Megafloid' by reducing the thickness of the gear and making it smaller in the outer diameter by which the pumping loss gets reduced and gets more discharge volume theoretically.…”
Section: Introductionmentioning
confidence: 99%